Spatial Modeling of Calanus finmarchicus and Calanus helgolandicus: Parameter Differences Explain Differences in Biogeography - Wilson, Robert J.; Heath, Michael R.; Speirs, Douglas C. (Frontiers in Marine Science, 2016)
The North Atlantic copepods Calanus finmarchicus and C. helgolandicus are moving north in response to rising temperatures. Understanding the drivers of their relative geographic distributions is required in order to anticipate future changes. To explore this, we created a new spatially explicit stage-structured model of their populations throughout the North Atlantic. Recent advances in understanding Calanus biology, including U-shaped relationships between growth and fecundity and temperature, and a new model of diapause duration are incorporated in the model. Equations were identical for both species, but some parameters were species-specific. The model was parameterized using Continuous Plankton Recorder Survey data and tested using time series of abundance and fecundity. The geographic distributions of both species were reproduced by assuming that only known interspecific differences and a difference in the temperature influence on mortality exist. We show that differences in diapause capability are not necessary to explain why C. helgolandicus is restricted to the continental shelf. Smaller body size and higher overwinter temperatures likely make true diapause implausible for C. helgolandicus. Known differences were incapable of explaining why only C. helgolandicus exists southwest of the British Isles. Further, the fecundity of C. helgolandicus in the English Channel is much lower than we predict. We hypothesize that food quality is a key influence on the population dynamics of these species. The modelling framework presented can potentially be extended to further Calanus species.